Adult alcohol drinking and emotional tone are mediated by neutral sphingomyelinase during development in males - Kalinichenko, Liubov; Mühle, Christiane; Jia, Tianye; Anderheiden, Felix; Datz, Maria; Eberle, Anna-Lisa; Eulenburg, Volker; Granzow, Jonas; Hofer, Martin Jürgen; Hohenschild, Julia; Huber, Sabine; Kämpf, Stefanie; et al. (Cerebral Cortex, 2022)
Alcohol use, abuse, and addiction, and resulting health hazards are highly sex-dependent with unknown mechanisms. Previously, strong links between the SMPD3 gene and its coded protein neutral sphingomyelinase 2 (NSM) and alcohol abuse, emotional behavior, and bone defects were discovered and multiple mechanisms were identified for females. Here we report strong sex-dimorphisms for central, but not for peripheral mechanisms of NSM action in mouse models. Reduced NSM activity resulted in enhanced alcohol consumption in males, but delayed conditioned rewarding effects. It enhanced the acute dopamine response to alcohol, but decreased monoaminergic systems adaptations to chronic alcohol. Reduced NSM activity increased depression- and anxiety-like behavior, but was not involved in alcohol use for the self-management of the emotional state. Constitutively reduced NSM activity impaired structural development in the brain and enhanced lipidomic sensitivity to chronic alcohol. While the central effects were mostly opposite to NSM function in females, similar roles in bone-mediated osteocalcin release and its effects on alcohol drinking and emotional behavior were observed. These findings support the view that the NSM and multiple downstream mechanism may be a source of the sex-differences in alcohol use and emotional behavior.
CRIS-Team WoS Importer:2022-04-15
Keywords: neutral sphingomyelinase; osteocalcin; depression; alcohol; anxiety

Association of a CAMK2A genetic variant with logical memory performance and hippocampal volume in the elderly - Rhein, Cosima; Mühle, Christiane; Lenz, Bernd; Richter-Schmidinger, Tanja; Kogias, Georgios; Boix, Fernando; Lourdusamy, Anbarasu; Dörfler, Arnd; Peters, Oliver; Ramirez, Alfredo; Jessen, Frank; Maier, Wolfgang; et al. (Brain Research Bulletin, 2020)
Calcium/Calmodulin-dependent kinase alpha (αCaMKII) has been shown to play an essential role in synaptic plasticity and in learning and memory in animal models. However, there is little evidence for an involvement in specific memories in humans. Here we tested the potential involvement of the αCaMKII coding gene CAMK2A in verbal logical memory in two Caucasian populations from Germany, in a sample of 209 elderly people with cognitive impairments and a sample of 142 healthy adults. The association of single nucleotide polymorphisms (SNPs) located within the genomic region of CAMK2A with verbal logical memory learning and retrieval from the Wechsler Memory Scale was measured and hippocampal volume was assessed by structural MRI. In the elderly people, we found the minor allele of CAMK2A intronic SNP rs919741 to predict a higher hippocampal volume and better logical memory retrieval. This association was not found in healthy adults. The present study may provide evidence for an association of a genetic variant of the CAMK2A gene specifically with retrieval of logical memory in elderly humans. This effect is possibly mediated by a higher hippocampal volume.
CRIS-Team Scopus Importer:2020-05-22
Keywords: adults; CAMK2A; elderly; hippocampus; logical memory; αCaMKII

Disrupted-in-Schizophrenia 1 (DISC1) Overexpression and Juvenile Immune Activation Cause Sex-Specific Schizophrenia-Related Psychopathology in Rats - Uzuneser, Taygun; Speidel, Jil; Kogias, Georgios; Wang, An-Li; Silva, Maria A. De Souza; Huston, Joseph P.; Zoicas, Iulia; von Hörsten, Stephan; Kornhuber, Johannes; Korth, Carsten; Müller, Christian P. (Frontiers in Psychiatry, 2019)
Synaptic pruning is a critical refinement step during neurodevelopment, and schizophrenia has been associated with overpruning of cortical dendritic spines. Both human studies and animal models implicate disrupted-in-schizophrenia 1 (DISC1) gene as a strong susceptibility factor for schizophrenia. Accumulating evidence supports the involvement of DISC1 protein in the modulation of synaptic elimination during critical periods of neurodevelopment and of dopamine D2-receptor-mediated signaling during adulthood. In many species, synaptic pruning occurs during juvenile and adolescent periods and is mediated by microglia, which can be over-activated by an immune challenge, giving rise to overpruning. Therefore, we sought to investigate possible interactions between a transgenic DISC1 model (tgDISC1) and juvenile immune activation (JIA) by the bacterial cell wall endotoxin lipopolysaccharide on the induction of schizophrenia-related behavioral and neurochemical disruptions in adult female and male rats. We examined possible behavioral aberrations along three major symptom dimensions of schizophrenia including psychosis, social and emotional disruptions, and cognitive impairments. We detected significant gene environment interactions in the amphetamine-induced locomotion in female animals and in the amphetamine-induced anxiety in male animals. Surprisingly, gene environment interactions improved social memory in both male and female animals. JIA alone disrupted spatial memory and recognition memory, but only in male animals. DISC1 overexpression alone induced an improvement in sensorimotor gating, but only in female animals. Our neurochemical analyses detected sex- and manipulation-dependent changes in the postmortem monoamine content of animals. Taken together, we here report sex-specific effects of environment and genotype as well as their interaction on behavioral phenotypes and neurochemical profiles relevant for schizophrenia.
CRIS-Team WoS Importer:2019-04-18

Neutral sphingomyelinase mediates the co-morbidity trias of alcohol abuse, major depression and bone defects - Kalinichenko, Liubov; Mühle, Christiane; Jia, Tianye; Anderheiden, Felix; Datz, Maria; Eberle, Anna-Lisa; Eulenburg, Volker; Granzow, Jonas; Hofer, Martin Jürgen; Hohenschild, Julia; Huber, Sabine; Kämpf, Stefanie; et al. (Molecular Psychiatry, 2021)
Mental disorders are highly comorbid and occur together with physical diseases, which are often considered to arise from separate pathogenic pathways. We observed in alcohol-dependent patients increased serum activity of neutral sphingomyelinase. A genetic association analysis in 456,693 volunteers found associations of haplotypes of SMPD3 coding for NSM-2 (NSM) with alcohol consumption, but also with affective state, and bone mineralisation. Functional analysis in mice showed that NSM controls alcohol consumption, affective behaviour, and their interaction by regulating hippocampal volume, cortical connectivity, and monoaminergic responses. Furthermore, NSM controlled bone–brain communication by enhancing osteocalcin signalling, which can independently supress alcohol consumption and reduce depressive behaviour. Altogether, we identified a single gene source for multiple pathways originating in the brain and bone, which interlink disorders of a mental–physical co-morbidity trias of alcohol abuse—depression/anxiety—bone disorder. Targeting NSM and osteocalcin signalling may, thus, provide a new systems approach in the treatment of a mental–physical co-morbidity trias.
CRIS-Team Scopus Importer:2021-10-08

Personality driven alcohol and drug abuse: new mechanisms revealed - Skóra, Maria Nalberczak; Pattij, Tommy; Beroun, Anna; Kogias, Georgios; Mielenz, Dirk; de Vries, Taco; Radwanska, Kasia; Müller, Christian P. (Neuroscience and Biobehavioral Reviews, 2020)
While the majority of the regular consumers of alcohol controls their consumption well over life span and even takes instrumentalization benefits from it, a minority, but yet high total number of users develops an alcohol addiction. It has long been known that particular personality types are more addiction prone than others. Here we review recent progress in the understanding of neurobiological pathways that determine personality and facilitate drug abuse. Novel approaches to characterize personality traits leading to addiction proneness in social settings in mice are discussed. A common genetic and neurobiological base for the behavioural traits of sensation seeking or a depressed phenotype and escalating alcohol consumption are reviewed. Furthermore, recent progress on how social and cognitive factors, including impulsivity and decision making, act at brain level to make an individual more vulnerable to alcohol abuse, are discussed. Altogether, this review provides an update on brain mechanisms underlying a broad spectrum of personality traits that make an individual more prone to alcohol and drug abuse and addiction.
CRIS-Team Scopus Importer:2020-06-30
Keywords: addiction; alcohol; depression; drug abuse; drug instrumentalization; impulsivity; personality; sensation-seeking

Swiprosin-1/ EFhd2: from Immune Regulator to Personality and Brain Disorders - Kogias, Georgios; Kornhuber, Johannes; Reimer, Dorothea; Mielenz, Dirk; Müller, Christian P. (Neurosignals, 2019)
BACKGROUND/AIMS: Swiprosin-1/ EF-hand domain 2 (EFhd2) is a Ca2+ sensor protein that plays an important role in the immune system. Its abundant expression in the brain, however, suggested also a role in neuronal circuits and behavior. METHODS: Here we review recent discoveries on the structure and molecular function, its role in immunity and its function in the brain regarding behavioral control and pathologies. RESULTS: While EFhd2 did not emerge as a vital protein for brain development, changes in its expression may nevertheless shape the adult behavioral repertoire significantly and contribute to adult personality traits. A defective function of EFhd2 may also render individuals more prone to the development of psychiatric disorders. Most prominently, EFhd2 proved to be a resilience factor protecting from fast establishment of drug addiction. Moreover, EFhd2 is critical for adult neurogenesis and as a modulator of monoaminergic systems. CONCLUSION: Dysregulated activity of EFhd2 is increasingly considered as a contributing factor for the development of numerous neurodegenerative disorders. Whether EFhd2 can be used as biomarker or in therapeutic approaches has to be addressed in future research.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Swiprosin-1; EFhd2; Immunity; Personality; Neurogenesis; Dopamine; Addiction; Neurodegenerative disorders

Swiprosin1/EFhd2 is involved in the monoaminergic and locomotor responses of psychostimulant drugs - Kogias, Georgios; Zheng, Fang; Kalinichenko, Liubov; Kornhuber, Johannes; Alzheimer, Christian; Mielenz, Dirk; Müller, Christian P. (Journal of Neurochemistry, 2020)
Psychostimulants are widely abused drugs that may cause addiction in vulnerable individuals. While the reward circuitry of the brain is involved in addiction establishment, various pathways in the brain may provide protection at the molecular level that limits the acute and chronic effects of drugs. These targets may be used for strategies designed to prevent and treat addiction. Swiprosin-1/EF hand domain 2 (EFhd2) is a Ca2+-binding cytoskeletal adaptor protein involved in sensation-seeking behaviour, anxiety and alcohol addiction. Here, we tested how EFhd2 contributes to the physiological and behavioural effects of the psychostimulant drugs methamphetamine (METH) and cocaine. An in vivo microdialysis study in EFhd2 knockout mice revealed that EFhd2 controls METH- and cocaine-induced changes in extracellular dopamine, serotonin and noradrenaline levels through different mechanisms in the nucleus accumbens and prefrontal cortex. Electrophysiological recordings in a slice preparation showed that a lack of EFhd2 increases dopaminergic neuronal activity in the ventral tegmental area and increases the sensitivity of neurons to stimulation. We report a role of EFhd2 in METH-induced locomotor activation and in the conditioned locomotor effects. No role, however, was observed in the establishment of METH- or cocaine-induced conditioned place preference. These findings may suggest that EFhd2 modulates the activity of the dopaminergic system and the neurochemical effects of METH and cocaine, which translate into a modulation of the behavioural effects of these drugs at the level of the acute and conditioned locomotor activity. (Figure presented.).
CRIS-Team Scopus Importer:2020-02-14
Keywords: cocaine; dopamine; EFhd2; methamphetamine; noradrenaline; serotonin; Swiprosin-1